CyberReco:~Cybersecurity Workforce Readiness Recommender System - Ramoni Lasisi (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Using the United States National Initiative for Cybersecurity Education framework as a guide, we propose CyberReco - Cybersecurity Workforce Readiness Recommender System, an AI/ML model that attempts to address readiness gaps needed to prepare users lacking in some cybersecurity knowledge, skills, and activities to be workforce-ready. CyberReco is built using natural language processing. We present a hierarchical-based framework that is composed of four components including, text preparation and normalization, keywords extraction and processing, similarity scores and skills computation, and a recommender component.